2016
DOI: 10.7554/elife.18633
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the differing roles of the β1 and β3 transmembrane and cytoplasmic domains for integrin function

Abstract: Integrins are transmembrane receptors composed of α and β subunits. Although most integrins contain β1, canonical activation mechanisms are based on studies of the platelet integrin, αIIbβ3. Its inactive conformation is characterized by the association of the αIIb transmembrane and cytosolic domain (TM/CT) with a tilted β3 TM/CT that leads to activation when disrupted. We show significant structural differences between β1 and β3 TM/CT in bicelles. Moreover, the ‘snorkeling’ lysine at the TM/CT interface of β s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 65 publications
(109 reference statements)
5
35
0
1
Order By: Relevance
“…The homology model began with the entire cytoplasmic domains of both αv and β3 as α-helical, yet we observed that only αv V993-V1024 and β3 D718-N769 had persistent α-helical structure with the remaining regions in extended conformations. This is consistent with NMR measurements of a β3 TM-cytoplasmic construct in DHPC:DMPC bicelles where β3 was helical through residue A737, well beyond the TM domain and into the cytoplasm (24). Also consistent with this NMR study, K713 (numbered K716 in ref.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The homology model began with the entire cytoplasmic domains of both αv and β3 as α-helical, yet we observed that only αv V993-V1024 and β3 D718-N769 had persistent α-helical structure with the remaining regions in extended conformations. This is consistent with NMR measurements of a β3 TM-cytoplasmic construct in DHPC:DMPC bicelles where β3 was helical through residue A737, well beyond the TM domain and into the cytoplasm (24). Also consistent with this NMR study, K713 (numbered K716 in ref.…”
Section: Discussionsupporting
confidence: 89%
“…Our MD simulations are also consistent with numerous experimentally reported features of the αvβ3 cytosolic and juxtamembrane regions (24,36). The homology model began with the entire cytoplasmic domains of both αv and β3 as α-helical, yet we observed that only αv V993-V1024 and β3 D718-N769 had persistent α-helical structure with the remaining regions in extended conformations.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Among 24 different integrin isoforms, the α ν β 3 and α 5 β 1 integrins, have important, but potentially separate roles in the assembly of adhesions and the physiology of many cell types [21,23,32–34,2431]. Nanoscale differences in physical properties between α ν β 3 and α 5 β 1 integrins can determine how nascent adhesions assemble [35], their organization [3638], transmitted traction [30,39] and lifetime [40], on account of their different properties. For example, it has been reported that the rate of integrin activation, k a , determines the number of integrins per adhesion [22,41], while lateral clustering, or avidity, E II , increases the size of individual adhesions [22,4244].…”
Section: Introductionmentioning
confidence: 99%